Rancang Bangun Aplikasi Point Of Sale Berbasis Web Dengan Pencatatan Stok Berbasis Android Menggunakan Model Waterfall - Riswan Ardiansah; Intan Kumalasari (CV. Multi Kreasi Media, 2024)
Pd Jaya Makmur Sentosa is a company engaged in the fish retail sector. As long as the company operates until now, it still uses a recording system by recording it in a book, and it is still not computerized, so that transactions and stored goods data are still not efficient and effective. In managing transactions and data on goods, they still record them using notes and ledger records. This results in several problems, namely that it is difficult to find invoices and calculate stock. Store owners find it difficult to check on business activities that occur, so it takes a long time and is ineffective. This research aims to build a point-of-sale application for Pd Jaya Makmur Sentosa. For this reason, a software development process is carried out based on correct software engineering. The method used in this study uses the waterfall model as a reference in its development. The results of this study show that it makes it easier to manage transactions and stock and records the entry and exit of goods more efficiently. Based on these findings, it is possible to conclude that the purpose of this research is to assist shop owners and employees in managing transactions and stock in accordance with the needs of shop owners in order to assist their business operations.